Final Report Radio Talk shows for the OND2024 Rainy season - International Livestock Research Institute; Kenya Meteorological Department (International Livestock Research Institute, 2024)
ILRI supported Kenya Meteorological Department (KMD) for Radio talk shows for dissemination of OND 2024 seasonal Agro-weather advisories. The talk shows were County-based and used local FM stations. There were three talk shows (1-1 1.2 hr each) where County staff from KMD, Agriculture and livestock departments attended. The officers used the adverts to provide advisories to farmers within the County in relation to the OND2024 rainy Season. The targeted no. of farmers expected to listen to the advisories were 400,000. The Counties covered were Kitui, Makueni, Kilifi and Baringo